The Impact of Road Right-of-Way Utilization on Road Performance: A Case Study of the Muradi Road Section, Sungai Penuh City, Jambi - Yuskal Despian; Eva Rita; Zuherna Mizwar (PT. Radja Intercontinental Publishing, 2026)
The inappropriate use of roadside space (Rumija) can cause lateral obstructions and reduce traffic performance. This study aims to identify the forms and intensity of Rumija use, analyse the performance of Muradi Road in Sungai Penuh, analyse its impact on road performance, and formulate management strategies. The study employed a quantitative approach with a descriptive-evaluative design. Data were obtained through observation of Rumija, road geometric measurements, surveys of traffic volume and lateral obstructions, documentation, and interviews with three expert informants. The analysis of the road section's performance was based on the 2023 Indonesian Road Performance Index (PKJI), whilst the management strategies were formulated based on expert judgement using the Plan-Do-Check-Act (PDCA) approach. The research findings indicate that the use of Rumija is not yet in line with its intended function, primarily due to parking on the carriageway and road shoulders, street vendor activities and motorcycle taxi stands on the pavements, as well as blocked drainage systems. The maximum traffic volume reached 2,082.8 vehicle-passes per hour with an effective capacity of 1,689.9 vehicle-passes per hour. The degree of saturation ranged from 0.86 to 1.16, the average speed was 12.5 km/h, and the Level of Service (LOS) was D-F. Side obstructions were predominantly caused by vehicles entering and exiting the road, accounting for 35 per cent. Management strategies include parking control, the reorganisation of street vendors, the restoration of pavements, drainage improvements, and strengthened inter-agency coordination. Road performance needs to be improved through the restoration of the Rumija's function and the integrated and sustainable control of ancillary activities.